PENGARUH LATIHAN KEKUATAN OTOT TUNGKAI TERHADAP JUMP SERV DALAM PERMAINAN BOLA VOLI DI EKSTRAKURIKULER SMK NEGERI 1 KUNINGAN - Riza Rizky Pratama, Riza; Rahman, Ramdhani; Wahidi, Ribut (STKIP Muhammadiyah Kuningan, 2025)
Riza Rizki Pratama (NIM. 182223099), The Effect of Limb Muscle Strength on Jump Serv in Extracurricular Volleyball Game at SMK Negeri 1 Kuningan, Health and Recreation Physical Education Study Program, 2022. This study aims to determine the effect of leg muscle strength training on serv jumps in extracurricular volleyball games at SMK Negeri 1 Kuningan. This research uses the Pre Experimental Design research method. The population and sample in this study were students of SMK Negeri 1 Kuningan who took part in volleyball extracurricular which opened 20 students. The instrument used in this study used a muscle strength test with a jump shoot accuracy test. The data analysis technique of this study tested normality, homogeneity and T test using SPSS-21. Results Based on research and data analysis, it was found that there was an effect of skipping exercise on increasing jump serv skills in students who took volleyball extracurricular activities at SMKN 1 Kuningan. Based on the paired sample t-test table, it is known that the value of sig (2-tailed) is 0.000. Because the value of sig ( 2-tailed ) 0.000 < 0.05 , thus Ha is rejected and Ho is accepted. Thus, skipping exercise is an exercise method that can be used to improve jump service skills in volleyball games.